2013
DOI: 10.1103/physreve.88.052708
|View full text |Cite
|
Sign up to set email alerts
|

Concentration-dependent like-charge pairing of guanidinium ions and effect of guanidinium chloride on the structure and dynamics of water from all-atom molecular dynamics simulation

Abstract: An all-atom molecular dynamics simulation shows concentration-dependent like-charge ion pairing of the guanidinium ion in an aqueous solution of guanidinium chloride. We have observed two types of like-charge ion pairing for guanidinium ions, namely, stacked ion pairs and solvent-separated ion pairs. Interestingly, both of these like-charge ion-pair formations are dependent on the concentration of guanidinium chloride in water. The probability of stacked like-charge ion-pair formation decreases, whereas, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 51 publications
(67 reference statements)
4
21
0
Order By: Relevance
“…Figure shows oxygen‐oxygen radial distribution functions, gOOtrue(rtrue) obtained from molecules placed by Dowser++ into protein structures from the united data set. The radial distribution function in Figure 7 has a sharp peak at 2.8 Å and another peak of a lower height at 4.6 Å due to tetrahedral arrangement of water . This is in approximate agreement with gOOtrue(rtrue) obtained from experimental diffraction results for liquid water .…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Figure shows oxygen‐oxygen radial distribution functions, gOOtrue(rtrue) obtained from molecules placed by Dowser++ into protein structures from the united data set. The radial distribution function in Figure 7 has a sharp peak at 2.8 Å and another peak of a lower height at 4.6 Å due to tetrahedral arrangement of water . This is in approximate agreement with gOOtrue(rtrue) obtained from experimental diffraction results for liquid water .…”
Section: Resultssupporting
confidence: 85%
“…The radial distribution function in Figure 7 has a sharp peak at 2.8 Å and another peak of a lower height at 4.6 Å due to tetrahedral arrangement of water. 29,30 This is in approximate agreement with g OO r ð Þ obtained from experimental diffraction results for liquid water. 31-34 Thus it appears that the placed water molecules are not overcrowded, judging by the position of the first pick, but distributed rather similarly to the liquid state.…”
Section: Optimized Dowser11supporting
confidence: 87%
“…The intrachain (and we will see later the interchain as well) association observed in the PHMB chain can be related to the remarkable like-charge pairing properties demonstrated for free guanidinium ions in previous experimental and computational studies. According to these studies, the association of the like-charged cations stems from hydrophobic attraction which overcomes the electrostatic repulsion. In particular, it was shown that hydrogen bonds are formed between the oxygen atoms of the water molecules and the nitrogen atoms of the ions but not between the water and the carbon atoms (despite their relative high charge) and therefore the cations (which have a planar symmetry) behave as hydrophobic surfaces .…”
mentioning
confidence: 58%
“…In this case, when n < 4, we have used proper normalization (see Bandyopadhyay et al 60 for details). So, the rapid decrease in ⟨q 4 ⟩ as a function of GdmCl concentration that was observed earlier 51 should not be attributed to breaking of tetrahedral network of water but, on the contrary, it is due to selection of wrong water neighbors. Those water molecules residing in the second shell of a central water molecule contribute to the decrease in ⟨q 4 ⟩.…”
Section: The Journal Of Physical Chemistry Bmentioning
confidence: 82%